2018
DOI: 10.1016/j.ihj.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Global longitudinal strain, ejection fraction, effort tolerance and normal echocardiography measurements in healthy Indians

Abstract: Introduction Normative comprehensive echocardiographic measurements data for healthy Indians are not available while data for American and European population is available from American Society of echocardiography and European Society of Cardiology/European Association of Cardio-Vascular Imaging and their publications. Available studies of Indian subjects are small and report only limited measurements with focus on left ventricular (LV) volumes. Objective We aim to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 10 publications
5
19
2
Order By: Relevance
“…Sullere et al presented the data of 707 subjects from a single center from central India. 10 This is the first study reporting normative echocardiographic values from eastern India and the largest Indian sample studied till date for the same. The wide spectrum of data among these contemporary studies involving Indian subjects re-asserts the influence of race, ethnicity, heredity, lifestyle and BSA on echocardiographic parameters even within a single country.…”
Section: Discussionmentioning
confidence: 99%
“…Sullere et al presented the data of 707 subjects from a single center from central India. 10 This is the first study reporting normative echocardiographic values from eastern India and the largest Indian sample studied till date for the same. The wide spectrum of data among these contemporary studies involving Indian subjects re-asserts the influence of race, ethnicity, heredity, lifestyle and BSA on echocardiographic parameters even within a single country.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the Japanese Normal Values for Echocardiographic Measurements Project (JAMP) study examined 700 healthy Japanese subjects and found that LV dimensions were larger for males than for females, but also showed that values for males were smaller when indexed to BSA, and that 2D LV volume for males was larger than for females even when the values were indexed to BSA [8]. Most of the subsequent national or regional studies on normal reference values for LV size showed results consistent with those of the JAMP study [9][10][11][12][13][14][15][16], while some showed only minor differences [17]. As for the relationship between LV size and age, 2D LV volume generally decreased with age for both genders [8,11,16,[18][19][20], which has been confirmed in a meta-analysis based [21].…”
Section: Sizementioning
confidence: 82%
“…LVM is generally larger for males than females even after indexation to BSA [8, 9, 11, 13-15, 17, 19, 20, 39]. LVM and LVM indexed to BSA (LVMI) were found to increase with age in many studies [8,14,[18][19][20][21], but one did not detect any relationship between LVMI and age [9]. The EchoNoRMAL study, a meta-analysis of normal echocardiographic reference values, demonstrated that LVMI was higher for European Whites than for Asians regardless of the measurement methods used [21].…”
Section: Massmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 773 studies were obtained from the literature search excluding duplicates, and after reviewing all abstracts, 102 studies passed initial screening for full-text review, and 44 studies were eligible for analysis , totaling 8,910 subjects (Figure 2) (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). In one study we were able to obtain unpublished means and standard deviations for LVGLS from the authors (15).…”
Section: Resultsmentioning
confidence: 99%